REWARD OR EQUITY CROWDFUNDING IN SPORT RELATED PROJECTS - Mădălina Camelia ADAM (Olteanu) (Universitaria Publishing House, Craiova, 2018)
In recent years, the crowdfunding method has generated several billions in funding, no matter the campaign's area of activity. Nevertheless, the efficiency of this tool may be improved, considering that around 60 percent of Kickstarter campaigns fail (Daly, 2017), considering this is probably one of the most popular and efficient global crowdfunding platforms. Through this article we have analyzed a variety of crowdfunding sport related campaigns or case studies, to discover common principles and patterns that may be repeated, to obtain the desired results. We have focused less on crowdfunding donation or non-profit sport projects (funding without expecting any return) and we have reviewed more sustainable forms, such as reward or equity crowdfunding, which involve receiving a reward or shares in the company in return for the investment. This article emphasizes that equity funding is used to a very small extent by the campaign's initiators (under 5% of all sport related projects), unlike reward crowdfunding. Some of the guiding principles and best practices common to the hundreds of projects reviewed are: • The ability to synthesize in one phrase the purpose of the product/project and its unique selling characteristics; • Complex grill for rewards, differentiated according to the donated amount; • Integrating the crowdfunding campaign in a larger marketing strategy; • For sport teams - using their existing fans as a source of external funds. The results of this research confirm some of the principles found in previous studies. It also provides additional information on the impact of this financing tool, regarding the obstacles met in the process or the state of development of jurisprudence in the field.